Strategies for Enhancing Service Satisfaction and Students' Retention in Private Secondary Schools: A Case Study in Iringa Municipality, Tanzania (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2024)
The study investigated the strategies for enhancing service satisfaction and student retention in private secondary schools in Iringa Municipality, Tanzania. It aimed to explore the levels of service satisfaction, identify the strategies for enhancement, and investigate interventions for retention. Using a case study design, 47 respondents participated, including 20 students, 8 parents, 4 school managers, and 8 head teachers, alongside 7 other education stakeholders. Data collection encompassed interviews, observation, and documentary reviews, with subsequent content analysis employed for data interpretation. The study’s findings highlight a concerning trend: low service satisfaction among customers within the selected schools. Despite existing strategies, the overall experience falls short of expectations. The study recommends that schools focus on designing and implementing internally driven strategies by considering the uniqueness of the needs of their students, conduct regular needs assessments to identify gaps and areas for improvement, implement a mechanism to track customer satisfaction continuously to make necessary adjustments through regular feedback, and schools should use customer satisfaction data to identify at-risk students.